Proposing Indonesia History Teaching that Transcends Political Ideologies - Nasution Nasution (Diponegoro University, 2022)
The teaching of Indonesian history, in many cases in school, remains dominated by history of politics and political indoctrination, underscoring the need for critical and holistic learning. This paper aims to analyze the Indonesian National History textbooks used in schools, and to examine the possibility of teaching Indonesian history that goes beyond political indoctrination and is holistic. The method used in this paper is the analysis of an Indonesian National History textbooks that have been used as the main textbook for the history subject in schools. The teaching of Indonesian history in schools is still dominated by a single version of historical events. The narratives of Indonesian history lessons often ignore different perspectives, or other aspects of historical events that are of interest. Indonesian history does not only belong to the winners. A holistic approach to the teaching of history is expected to help enrich students' knowledge of past events and provide a clearer picture of the history of a multicultural society. For example, a discussion of the Benteng economic policy should not only revolve around the points of view of one ethnic group and ignore the suffering of others. In other cases, discussions on the PKI revolt often neglect human rights aspects, et cetera. Not only should students gain knowledge about past events based on the dominant interpretations, but are also exposed to the narratives of marginalized people. Not only that, history lessons should also cover aspects that include arts, literature, painting, music and other cultural products. In the end, a holistic approach enriches students’ understanding of a historical event, foster a positive attitude and inspire them to learn about stories that have been under-heard or deliberately marginalized.